2022
DOI: 10.1111/ggi.14365
|View full text |Cite
|
Sign up to set email alerts
|

Environmental hazards as risk factors for trips and slips at home among Japanese older people: A pilot study toward the development of a self‐assessment tool for the home environment

Abstract: Aim Housing structures differ according to the local culture, climate, and lifestyle, and these unique characteristics usually act as potential hazards for falls, trips, and slips. The purpose of this study was to identify environmental hazards in a Japanese house and their association with falls, trips, and slips among older people. Methods A total of 97 older people aged ≥75 years were included in this cross‐sectional study. The number of environmental hazards was measured using a 46‐item tool designed speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This scale has strong operability and high practicability in all adult patients in the clinic. Studies have shown that its sensitivity and specificity for predicting fall-induced injuries are 100% and 65.9%, respectively [7][8][9][10]. However, this scale has not been validated in patients with AMI after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…This scale has strong operability and high practicability in all adult patients in the clinic. Studies have shown that its sensitivity and specificity for predicting fall-induced injuries are 100% and 65.9%, respectively [7][8][9][10]. However, this scale has not been validated in patients with AMI after PCI.…”
Section: Introductionmentioning
confidence: 99%